Rising Islamophobia in Europe and the Clash of Civilization Theory - Aktas, Murat (Ankara Univ European Union Research Centre, 2014)
The end of the Cold War has included major changes in international politics and Islam has rapidly replaced communism in the role of principal enemy of the Western world. The Clash of Civilizations theory has been used as one of the main instruments of the conflict between Islam and Western world. This theory contends that in the post-Cold War world the crucial distinctions between people will be cultural rather than ideological or economical. According to this theory the 21st century will witness struggles between Western civilization and others, especially the Western, Islamic and Confucian civilizations. Therefore, the statistics reflect that a strong social, cultural and economic discrimination and intolerance against Muslim inhabitants called Islamophobia has gradually spread to the European countries since the end of the Cold War. This article aims to analyze the relationships between rising Islamophobia, in Europe and The Clash of Civilisations theory.
Keywords: Clash of Civilizations; Islamophobia; Islam and Europe